POTRET PENDIDIKAN ENTERPREUNER DI PESANTREN - Yuniatul Jannah; Siswanto Siswanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This study focuses on the contribution of Islamic boarding schools in producing various entrepreneurial cadres. This research is a qualitative research with the type of case study research. Sources of research data from primary data sources (students, teachers, kyai) and secondary data (documentation). Data collection techniques are interviews, observation and documentation. Data analysis techniques with three forms of analysis, namely data reduction, data presentation and drawing conclusions. The conclusion of the research is that the portrait of entrepreneur education is imbued with five souls which are implemented in every step, movement, in the curriculum and education system of the santri together with the kyai caregivers and their assistants, the five souls are sincerity, simplicity, independence, brotherhood and freedom. Entrepreneur education methods are uswah, suhbah and da'wah methods. The supporting factors are the 24-hour mukim system, the cooperation of teachers and students, control and evaluation by the leadership. The inhibiting factors are facilities and infrastructure as well as costs.